Acute NaCl Loading Reveals a Higher Blood Pressure for a Given Serum Sodium Level in African American Compared to Caucasian Adults - Wenner, Megan M.; Paul, Erin P.; Robinson, Austin T.; Rose, William C.; Farquhar, William B. (Frontiers in Physiology, 2018)
Purpose: Black individuals are more prone to salt-sensitive hypertension than white individuals. Small changes in serum sodium (Na+) result in increased blood pressure (BP). However, it remains unclear if there are racial differences in BP responsiveness to increases in serum Na+. Therefore, the purpose of this investigation was to determine if black adults have altered BP responsiveness to acute changes in serum Na+ compared to white adults. Methods: We measured beat-by-beat BP, serum Na+, plasma renin activity (PRA), angiotensin II (Ang II), and aldosterone (Aldo) during a 60-minute 3% NaCl infusion (hypertonic saline infusion, HSI) in 39 participants (19 black, age: 23±1, 20 white, age: 25±1). Data reported as black vs. white cohort, Mean ± SEM. Results: Baseline BP and serum Na+ were similar between groups and increased during HSI in both black and white participants (p<0.01). However, the peak change in serum Na+ was greater in black participants (Δ6.01±0.34 vs Δ4.85±0.38 mmol/L, p=0.03). There was a significant group effect (p=0.02) and an interaction between race and serum Na+ on systolic BP (p=0.02). Larger categorical changes in serum Na+ corresponded to changes in systolic BP (p<0.01) and black participants demonstrated greater systolic BP responses for a given categorical serum Na+ increase (p<0.01). Baseline Aldo was lower in black adults (7.2±0.6 vs. 12.0±1.9 ng/dL, p=0.03), there was a trend for lower baseline PRA (0.59±0.9 vs. 1.28±0.34 ng/mL/hour, p=0.07), and baseline Ang II was not different (14.2±1.8 vs. 18.5±1.4 pg/mL, p=0.17). PRA and Aldo decreased during the HSI (p≤0.01), with a greater decline in PRA (Δ-0.31±0.07 vs. Δ-0.85±0.25 ng/mL/hour, p<0.01) and Aldo (Δ-2.5±0.5 vs. Δ-5.0±1.1 ng/dL, p<0.01) in white participants. However, the racial difference in PRA (p=0.57) and Aldo (p=0.59) reduction were no longer significant following baseline covariate analysis. Conclusions: Black individuals demonstrate augmented serum Na+ to an acute hypertonic saline load and greater systolic BP responsiveness to a given serum Na+. The altered BP response may be attributable to lower basal PRA and Aldo and a subsequently blunted RAAS response during the HSI.